Integrating Islamic input in undergraduate psychiatry teaching: IIUM experience - Md Rosli, Najwa Hanim; Md Tahir, Mohd Faiz; Mat Zain, Nora; Mohd Noor, Hanisah; Abdullah, Kartini (2016)
Since the recognition of psychiatry as a medical specialty back in the 19th century, many theories, therapies and treatment were much influenced by Western findings and practice. Sigmund Freud recorded in his book, “Future of an Illusion”, that he portrayed faith in God as a “collective neurosis”. However, in 2012, the Royal College of Psychiatrists (London) affirmed the value of considering spirituality and religion as a part of good clinical practice and to benefit both the patient and the psychiatrist throughout the treatment period.